STRATEGI ADAPTASI PENDUDUK DI WILAYAH KEKERINGAN DESA SERIWE, KECAMATAN JEROWARU KABUPATEN LOMBOK TIMUR - , Mayang Rahmi Novita ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Kabupaten Lombok Timur suffers the disparity of regional development, but not caused by the drought conditions (Novitasari, 2013). Whereas, the economy of Kabupaten Lombok Timur rested on the primary sector, especially on agriculture. One of the most arid village in the Kecamatan Jerowaru is Desa Seriwe. Located on the coast and not have a ground water basin caused the inhabitants are not just suffering in agriculture but also in meeting their daily water needs. However, the number of inhabitants in this village was increasing from time to time. That indicates the existence of adaptations performed by inhabitants. Adaptation itself is an important effort related to the completion of the problem through a bottom-up approach. Therefore, the objectives of this study were to find the adaptation strategies performed by the inhabitants and to find the influential factors in those adaptation strategies. The research approach was inductive qualitative. The study of inhabitants adaptation strategies to drought in Desa Seriwe was basically a case study. Stated as a single case study because of the extreme condition and the uniqueness that occured in this case. The unit of analysis of this research was inhabitants adaptation of Desa Seriwe, Kecamatan Jerowaru to drought. The unit of observation was Desa Seriwe's inhabitants. The unit of information collection was the household or family. This research collected primary and secondary data. The primary data were obtained from interviews and direct observation. The secondary data were obtained from the documentation and archival documents. This research found two concepts of adaptation that performed by inhabitants of Desa Seriwe and one concept of influence factors. The two concepts of adaptation were divided based on the scope of influence and the type of action. The concept of adaptations based on the scope of influence consists of the direct adaptation and indirect adaptation. The concept of adaptation based on the type of action consists of active adaptation and passive adaptation. The concepts of factors that influence the inhabitants adaptation strategies are referred to internal factors and external factors.